Coastline evolution at Balneario Parque Mar Chiquita, Argentina - A Merlotto; GR Bértola (Ciencias Marinas, 2009)
This study determined coastline evolution and retreat rates at Balneario Parque Mar Chiquita (Argentina) between 1949 and 2007. The dune toe was considered the coastline indicator, and it was determined based on historical maps, aerial photographs, a satellite image, and field measurements. The analysis showed that the intensity of the erosion process has declined though it continues to be meaningful. The annual rate has decreased from 17.71 to 1.41 m yr–1, corresponding to a total retreat of 299.01 m in the last 58 years. The temporal variations of the phenomenon mainly result from changes in beach nourishment by the littoral drift, which has been affected by sand mining and coastal defenses built to the south of the study area. Different spatial behaviours were also registered in the town, associated with geomorphological characteristics and dune conservation state. Sudestada storms have played a significant role in the coastline retreat. The results contribute to the understanding of the magnitude and dynamics of the erosion process, and should be of use in the preparation of coastal management programs and risk evaluations.